Rationale for the prevention of mastitis in cows during the dry period and after calving - Andrii Berezovskyi; Artem Dovbnya; Oleksii Fotin; Dmytro Kisil; Bohdan Morozov (Наукові горизонти, 2023)
Testing cows for mastitis before starting and treating all milch cows with a long-acting antimicrobial agent is an important component of the preventive preparation of animals for the dry period. In addition, determining the sensitivity of pathogens isolated on the farm and rotating antimicrobials increases the effectiveness of therapy and reduces the risk of resistant strains of microorganisms. The purpose of this study was to determine the preventive and therapeutic effects of preparations based on povidone-iodine and cefquinome sulfate for cows with mastitis. The following methods were used in the study: calculation of the total number of somatic cells by flow cytometry; California test; sensitivity to antimicrobial agents by agar disks; clinical and physiological method; statistical method. During the examination of cows for mastitis, it was identified that in the control group the number of somatic cells averaged 450 thousand/cm3, the total number of microorganisms was 130 thousand. In cows of the experimental group, productivity was 23.6%, the number of somatic cells was 600 thousand/cm3, microorganisms – 550 thousand CFU/cm3. It was identified that the isolated microflora showed high sensitivity to the preparation based on povidone-iodine and cefquinome sulfate. Therefore, udder conservation for cows of the experimental group with signs of mastitis was conducted with a product based on povidone-iodine, which affected the increase in lactation and improvement of milk quality after calving. The criteria for milk in the experimental group at the end of the experiment corresponded to the grade extra – 30%, top – 60%, and first – 10%. As a result of the therapy, lactation improved in cows, and the quality of milk corresponded to the first grade. At the end of the study, the quality of milk in cows of the control group corresponded to the extra Grade – 10%, top – 40%, and first – 50%. The practical value of the study lies in the prevention of mastitis on the farm, improving the quality of the resulting products, reducing the cost of veterinary care and culling animals